2011
DOI: 10.1016/j.profoo.2011.09.177
|View full text |Cite
|
Sign up to set email alerts
|

Development of an impedance measurement system for the detection of decay of apples

Abstract: Main objective was the development of a non-contact measurement technique to determine the decayed proportion of apples. Using impedance measurements enables measuring the proportion of damaged cells in biological tissue depending on the frequency. The measurements with the coil system showed dependence on the mass and on the apple variety. With increasing decay the voltage signal also increased. Healthy apples can be distinguished statistically sure of partially decayed apples from a decayed part of 16.3%. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The a-dispersion (100 mHz -1 kHz) is due to surface admittance and depends principally on the external membrane surface and apoplastic structures (cell walls), while b-dispersion (1 kHz -1 MHz) is mainly associated with the internal membrane and intracellular structures. Results of earlier studies also confirmed our findings that especially the upper part of the a-dispersion and the lower part of the b-dispersion region (0.5-10 kHz) is suitable for the complex, extra-and intracellular electrical investigation of plant tissues and organs (Euring et al, 2011).…”
Section: Resultssupporting
confidence: 90%
“…The a-dispersion (100 mHz -1 kHz) is due to surface admittance and depends principally on the external membrane surface and apoplastic structures (cell walls), while b-dispersion (1 kHz -1 MHz) is mainly associated with the internal membrane and intracellular structures. Results of earlier studies also confirmed our findings that especially the upper part of the a-dispersion and the lower part of the b-dispersion region (0.5-10 kHz) is suitable for the complex, extra-and intracellular electrical investigation of plant tissues and organs (Euring et al, 2011).…”
Section: Resultssupporting
confidence: 90%
“…, Euring et al. ), potato and carrot (Zhang and Willison , , Angersbach et al. ), and eggplant (Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MI has been investigated recently in food technology, having the great advantage that electrodes are not needed for its application (Schivazappa et al, 2017). There are several studies in which the spectra of agricultural products have been analyzed using multi-frequency MI (Barai et al, 2012) and single-frequency MI (Euring et al, 2011). Regarding hams, Schivazappa et al (2017) obtained a higher signal in salted hams than in fresh ones, and they developed a model for salt prediction in which the RMSEC was 0.18%.…”
Section: Other Emerging Technologiesmentioning
confidence: 99%